Colloidal Plasmonic Nanoparticles for Ultrafast Optical Switching and Laser Pulse Generation - Liu, Xiaofeng (Frontiers in Materials, 2018)
Light-matter interactions are greatly enhanced and spatially well-confined in plasmonic nanostructures in the spectral resonance range. In colloidal plasmonic nanoparticle (NP), this effect is manifested by the strong absorption caused by the collective oscillation of conduction electrons in NPs, known as the localized surface plasmon resonance (LSPR). The strong spectral resonance due to LSPR also contributes to the large enhancement in optical nonlinearity, such as nonlinear absorption and optical Kerr effect, and the ultrafast transient photo-bleaching in those materials making them ideal platforms for exploring optical switching behavior that is needed in all optical devices. Here, we review the recent advances in the use of colloidal processed noble metal, metalloid, chalcogenide and oxide plasmonic NPs for ultrafast optical switches to drive pulse laser generation in both solid state and fiber lasers. The broadband and ultrafast response of these plasmonic NPs offers a significant advantage in devices performance and allows the pulse generation from near infrared (NIR) to middle infrared (MIR) spectral range with pulse duration down to 100-femtosecond level. Compared with commercial products and other optical switches based on 2D materials, these plasmonic NPs are expected to provide a competitive and cost-efficient material solution to compact ultrafast pulse lasers and relevant devices.